Financing Micro, Small and Medium Enterprises (MSMEs) in Ghana: A case study of Techiman Municipality - Sackey, Emmanuel O. (2016)
A dissertation submitted to the department of Accounting and Finance, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Business Administration (Finance)